Analyzing the Effect of Structural Differentiation and Inter-Organizational Relations on Organizational Ambidexterity with an Emphasis on the Mediating Role of the Organizational Platform to Increase Organizational Performance (Case Study: General Directorate of Sports and Youth of Ilam Province) - Peyman Akbari; Ali Karimi; Ibrahim Aeini (مدیریت نوآوری و راهبردهای عملیاتی)
Purpose: This research aims to analyze the effect of structural differentiation and inter-organizational relations on organizational ambidexterity, emphasizing organizational content's mediating role in increasing organizational performance.Methodology: The current research is applied in terms of purpose and descriptive survey in nature and method. The statistical population of this research includes 250 employees of the general department of sports and youth of Ilam province. One hundred fifty people were selected using Cochran's formula. The data collection tool is the governor's questionnaires in this field. The validity and reliability of the questionnaires also indicate that the measurement tools have good validity and reliability.Findings: The results of hypothesis testing by SMART-PLS 3.8 software and t-test statistics and path coefficients (β) showed that the structural differentiation on the organizational context and ambidexterity has a direct, significant, and medium effect, respectively; the direct and indirect impact is substantial and average. Also, inter-organizational relations have a direct, important, and moderate impact on the organizational context and ambidexterity, respectively; the direct and indirect effects are substantial and moderate. Also, the organizational content has a direct, significant, and moderate impact on organizational ambidexterity, and finally, organizational ambidexterity has a direct, significant, and moderate effect on organizational performance. Finally, the mediating role of organizational content was confirmed.Originality/Value: Based on the results, the managers and decision-makers of the said office can pay attention to the role of organizational ambidexterity to increase its organizational performance; of course, they should be able to, directly and indirectly, consider the role of variables such as structural differentiation, inter-organizational & organizational content pay attention. Why can these variables significantly affect organizational ambidexterity and increase organizational performance?